Materialisme dan Transformasi Sosial:Analisis Perubahan Kantor Pos Medan dalam Konteks Ekonomi - Harahap, Rosmawaty; Harianti, Inggit; Anggita, Dina; Juniar, Indi; Multhia, Muzkia; Feby, Salsabila; Hutabarat, Revalina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The problem in this study is how materialism affects the social transformation and function of the Medan post office in the context of economic change, as well as to examine the impact of materialism on changes in the function of the Medan post office. The data source of this research is taken from the literature using the Heuristic approach. The search and collection of sources regarding the problem under study. The goal is that researchers can produce quality research with as much information as possible. That Medan emerged as a city that was more advanced than other cities because it functioned as the center of government during the colonial period in the Kesawan area and its surroundings. In the area there were buildings that supported the economy at the time such as City hall,Merdeka square,Railway,Post Office,Bank Indonesia,Tip top restaurant,and other.